Study of Clogging Phenomenon for a Conical Hopper: The Influence of Particle Bed Height and Hopper Angle - Muhammad Hammad Khalid; Yixian Zhou (Science and Technology of Nuclear Installations)
The granular flow is one of the principal issues for the design of pebble bed reactors. Particularly, the clogging phenomenon raises an important issue for pebble bed reactors. In this paper, we conduct experiments and discrete particle simulation of two-dimensional discharge granular flow from a conical hopper, to study the effect of the particle bed height h and hopper angle α on the clogging phenomenon. In general, the clogging probability J increases with height h and starts to saturate when h is larger than a critical value. The experimental result trends are supported by discrete simulations. To understand the underlying physical mechanism, we conduct discrete particle simulations for various h values, focusing on the following parameters: the statistical averaging of the volume fraction, velocity, and contact pressure of particles near the aperture during the discharge. We found that, among all relevant variables, the contact pressure of particles is the main cause of the increasement of J when h increases. An exponential law between the pebble bed h and clogging probability J has been established based on these observations and Janssen model. As for hopper angle α, J shows an almost constant behavior for any rise in α followed by a sudden regression at α=75°. Surprisingly, the effect of α is most obvious for intermediate values of h, where we observe a sharp increasement of clogging probability. The same trend is observed in the two-dimensional discrete simulation results.